Faster than you think: Renewable energy and developing countries - Arndt, Channing; Arent, Doug; Hartley, Faaiqa; Merven, Bruno; Mondal, Md. Hossain Alam (Annual Reviews, 2019)
Since 2007, large and unexpected declines in generation costs for renewable energy systems, particularly solar but also wind, combined with policy measures designed to limit greenhouse gas emissions, have created a paradigm shift in energy systems. Variable renewable energy now dominates total investment in electricity power generation systems. This dominance of variable renewable energy in investment has thrust the systems integration task of matching electricity supply with demand to center stage, presenting new challenges for energy policy and planning as well as for the institutional organization of power systems. Despite these challenges, there is ample reason to believe that variable renewables will attain very high levels of penetration into energy systems, particularly in regions well endowed with solar and wind potential. Similar to their success with mobile phone telephony, many developing countries have a significant opportunity to leapfrog directly to more advanced energy technologies that are low cost, reliable, environmentally more benign, and well suited to serving dispersed rural populations.